Implementation of mobile journalism in the Spanish media - Martínez-Fresneda Osorio, Humberto; Zazo Correa, Laura; García Huertas, Juan Gabriel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The technological evolution of the newspaper industry has revolutionized journalism. Now the telephone has overcome the spatial barrier and information can be accessed anywhere and at any time, edited and created, and consume audio or video in any of its modalities. The latest surveys indicate that more than 90% of users connect via telephone to consume journalistic information. The design, edition and writing of the information undergoes a significant change: the concept of the traditional journalistic genre for new narratives that force the professional to acquire new skills.